The Regulation of Surface Freight Transportation: The Welfare Effects Revisited - Braeutigam, Ronald R.; Noll, Roger G. (The Review of Economics and Statistics, 1984)
This paper reexamines a much-studied topic, the effects of surface freight regulation. It demonstrates that several studies use invalid methods to estimate the welfare costs of rate regulation, develops a correct procedure, and provides estimates of the welfare effects using data and modal market share relationships estimated by Boyer. The paper also analyzes some implications of the common assumption that the demand for total freight shipments by all modes is perfectly inelastic.